(untitled) (Herald of the National Children’s Medical Center, 2025)
Background. To identify the clinical and functional characteristics of refractive amblyopia in children with cerebral palsy (CP) and to evaluate the effectiveness of a comprehensive ophthalmological correction program combining traditional and adapted therapeutic methods. Materials and methods. A prospective clinical study included 39 children (78 eyes) aged 3 to 12 years diagnosed with CP and confirmed refractive amblyopia. Visual impairment was assessed using adapted diagnostic techniques that took into account motor and cognitive limitations. Treatment included individually prescribed optical correction, occlusion therapy, hardware-based methods (Amblyotron), as well as speech and psychological support. Results. Following a six-month course of therapy, a statistically significant improvement in visual acuity (from 0.31 to 0.47; p<0.01), fixation stability, and oculomotor coordination was observed. More pronounced positive dynamics were noted in younger children and those with preserved cognitive function. It was also found that the severity of neurological deficits is a significant prognostic factor for therapeutic success. Conclusion. The findings highlight the necessity of a multidisciplinary approach and early intervention in the management of patients with CP and amblyopia.